Effectiveness of xylitol and polyol chewing gum on salivary streptococcus mutans in children: A randomized controlled trial - Eby Aluckal; Anil V Ankola (Wolters Kluwer Medknow Publications, 2018)
Introduction: Dental caries is a multi-factorial, infectious disease, the prevention of which is based on multifaceted approaches. Chewing sugar-free gum has potential beneficial effects on dental health. Objectives: The aim of this study is to assess and compare the effectiveness of xylitol and polyol chewing gums on salivary Streptococcus mutans in 12-15 years old schoolchildren residing in hostels in Belgaum city. The acceptability of the two chewing gums was also assessed. Materials and Methods: Sixty children of 12-15 year age groups from three hostels, who fulfilled all the inclusion criteria, were included in this triple blind randomized controlled field trial. They were then randomly allocated into one of the three groups using lottery method. Xylitol chewing gum, polyol chewing gum and control group (no chewing gum). Patients were instructed to chew one pellet two times a day after meals for 5 min each for 30 days. Salivary samples were collected at baseline, 30 days after chewing gum use and 30 days after discontinuation, for microbiological analysis. The data were subjected to statistical analysis using SPSS software version 18. Results: Chewing 100% xylitol chewing gum 2 times a day for 5 min for 30 days can successfully reduce salivary S. mutans counts. The xylitol gum has shown a maximum benefit against salivary S. mutans when compared to polyol gum and control group. Conclusion: Xylitol-containing chewing gums can be used as an adjunct to regular home care preventive procedures to prevent dental caries.